Three-dimensional Distribution of Muscle and Adipose Tissue of the Thigh at CT: Association with Acute Hip Fracture - Mühlberg, Alexander; Museyko, Oleg; Bousson, Vallrie; Pottecher, Pierre; Laredo, Jean-Denis; Engelke, Klaus (Radiology, 2019)
Purpose: To evaluate determinants of hip fracture by assessing soft-tissue composition of the upper thigh at CT.
CRIS-Team WoS Importer:2019-02-21